'Fair' inequality, consumption and climate mitigation. (15th February 2021) - Millward-Hopkins, Joel; Oswald, Yannick
Abstract: Economic inequality and climate change are pressing issues that have climbed high up the political agenda, yet action to mitigate both remains slow. As income is a key determinant of ecological impacts, the Global North—and wealthier classes elsewhere—are the primary drivers of global carbon emissions, while the least well off have contributed the least yet are set to be hit hardest by climate impacts. These inequalities are clearly unjust, but the interrelations between economic inequality and ecological impacts are complex, leaving open the question of whether reducing the former would mitigate the latter, in the absence of reductions in total economic output. Here, we contribute to these debates by estimating the carbon-footprint implications of reducing income (and hence expenditure) inequalities within 32 countries of the Global North to the levels people consider to be fair ; levels that are substantially smaller than currently exist. We find that realising these levels of economic inequality brings comparable reductions in carbon-footprint inequalities. However, in isolation, implementing fair inequalities has a negligible impact upon total emissions. In contrast, recomposing consumption—by reducing inequalities in household expenditure and the overall levels, then reallocating the reductions to public services—reduces carbon footprint by up to 30% in individual countries and 16% overall and, crucially, still allows the consumption of those at the bottom to rise. Such reductions could be significant on a global level, and they would be additional to the full range of conventional technological and demand-side measures to reduce carbon emissions.